Sumiala, J. (2022). Mediated Death - Costa, Bruno Frutuoso (2024)
Social platforms have increased the daily public visibility of death, mourning, and the digital presence of the dead, and the domestication of these technologies has led to the emergence of new mourning practices (Pasquali et al., 2022). In this hypermediated and hybrid context of the shared world (Deuze, 2014), death is not only institutionalised but also frequently mediated and negotiated in journalism, entertainment, social networks and media, and streaming services. This is the starting point of the work Mediated Death by Johanna Sumiala.